INTERPRETING THE INDONESIAN CONSTITUTIONAL COURT APPROACH IN CONDUCTING JUDICIAL REVIEW ON CASES RELATED TO ECONOMIC AND SOCIAL RIGHTS - Omara, Andy (Indonesia Law Review, 2017)
One of the duties of the Indonesian Constitutional Court (Mahkamah Konstitusi - MK) is to determine whether legislation is consistent with the Constitution. If the MK determines that a statute is inconsistent with the Constitution, it declares that such statute is invalid. In such instance, the MK has the final word to determine the validity of legislation. In the view of some scholars, this feature reflects that the MK adopts strong form of judicial review. While this assertion holds true in some cases, it does not necessarily reflect the complete feature of the MK’s approach in deciding cases. In some economic and social rights cases, the MK decision adopts weak form of judicial review. This paper attempts to explain that while constitutionally the MK adopts strong form of judicial review, in some economic and social rights cases it adopts weak form of judicial review.